Assessing the sound of a woodwind instrument that cannot be played. (1st January 2019) - Bowen, D. Keith; Buys, Kurijn; Dart, Mathew; Sharp, David
Abstract: Historical woodwind instruments in museums or private collections often cannot be played, by virtue of their poor condition or the risk of damage. Acoustic impedance measurements may usually be performed on instruments in good condition without risk of damage, but only if they are in playable condition: complete, with functioning mechanism, well-sealing pads and no open cracks. Many museum specimens are not in this condition. However, their geometry may almost always be accurately measured, and the measurements used to calculate the acoustic impedance as a function of frequency via a computer model of the body of the instrument. Conclusions may then be drawn about the instrument's pitch, intonation, temperament, fingerings, effects of bore shrinkage and even the timbre of the notes. A simple linear, plane- and spherical-wave computational model, originally developed for calculating the acoustic impedance of conical-bore woodwinds, is here applied to bass clarinets for the first time. The results are assessed by experimental impedance measurements and by playing tests on an historical Heckel bass clarinet in A of 1910 that has been continuously maintained in playing condition but has been relatively lightly used. The degree of agreement between the acoustic measurements and the calculations, the required measurement accuracy and the potential and limitations of the method are discussed, and specific conclusions for this instrument are drawn. Measurement of the frequencies produced in playing tests allowed us quantitatively to estimate the effects of mouthpiece and reed on the pitch of the produced notes. The method is shown to be a viable method for the examination of historical woodwind instruments.